PENGARUH MEDIA VISUAL POP UP BOOK MELALUI MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) PADA KEMAMPUAN LITERASI NUMERASI DI KELAS V SEKOLAH DASAR - Fadhli Dzil Ikrom; Fajar Yumanhadi Aripin; Nadila Maulina; Aisyah Banata; Dila Nurma Fadillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is entitled "The Effect of Pop Up Book Visual Media Through the Teams Games Tournament (TGT) Learning Model on Numeracy Literacy Skills in Grade V Elementary School". In this quantitative research, the researcher used experimental research to facilitate the data input process in the field (elementary school). In this Pre-Experimental research, the researcher determined the design, namely One Group Pretest Posttest Design. According to the results of the research input, the implementation of Team Games Tournament (TGT), a collaborative learning model enriched with pop-up books, has a positive impact on students' academic achievement. There was an average increase of 36.36 and a pre-test of 60.23 post-test, with a difference of 23.87 points. In the t-test testing, the critical value was less than 0.05 indicating a difference in academic achievement before and after implementation. With this N-Gain analysis of 0.4280; this figure corresponds to the median value. Although these results are not evenly seen in all students, with this the level of student knowledge has increased. Thus, there is an increase with the implementation of the TGT model through pop-up book media on students' numeracy literacy. However, further efforts are still needed to perfect all aspects of this teaching model.